Parâmetros bioquímicos e imunológicos associados ao risco cardiometabólico - Santos, Anna Lettycia Vieira dos (2014)
Cardiovascular disease is the leading cause of death worldwide, among them acute myocardial infarction is the most frequent and disabling pathologies. The progression of cardiovascular diseases involves genetic factors as well as other risk factors and modifiable acquired, inflammatory components of the immune response. The interactions between the immune system and abnormal metabolic conditions sustain and propagate a vicious cycle of chronic inflammation and metabolic dysfunction that are fundamental to the progression of diabetes and cardiovascular diseases. Regarding the problem the aim of this study was to evaluate the biochemical and immunological parameters, and associate with the risk of diabetes mellitus and cardiovascular diseases. The study initially included the participation 100 individuals of both sexes, aged ≥ 27 years. Upon completion of the screening (anthropometric measurements, fasting blood glucose levels and blood pressure levels) 25 participants followed for biochemical and immunological analyzes. They were then grouped according to the Framingham risk score in Control, Risk and Low Risk group. In the statistical analysis used as a tool Bioestat the software. The study showed that the lipids and glucose levels increased compared to the control and calcium decreased. On immunological parameters (cytokines) we found that IL-6 increased compared to control and TNF-α and IL-17A decreased. After the analysis we conclude that the low risk group is more exposed compared to control , requiring special attention due to the increased risk for diabetes mellitus 2 and later cardiovascular deterioration as they present considerable changes in anthropometric and biochemical parameters, soon to reflect the immunological profile, but are still asymptomatic and silent